Snack of students in secondary schools and their buffet conditions in Tehran: A qualitative study - Esfarjani, F; Zoghi, T; Roustaee, R; Mohammadi Nasrabadi, F; slami Amirabadi, M; Kamrani, Z; Hadjifaraji, M (Advances in Nursing & Midwifery, 2009)
Background School buffets are considered as important facilities in providing snacks for students. In addition, the consumption of junk and unhealthy foods in the snacks is prevalent. Purpose This qualitative study was carried out to identify the views and performance of students concerning having breakfast as well as snacks and assessing school buffets in Tehran in 2006. Methods 240 students from 12 secondary schools in district 4 of Tehran were selected by purposive sampling method. 24 focus group discussion sessions, each lasted 60 minutes with 8-10 students were held and recorded for each group. All session notes were compared and controlled by recorded files for identifying the main themes to be encoded, classified and analyzed. Results More than half of the students ate snacks to reduce lack of energy and satisfy hunger. About 50% of girls took cake, waffle and milk while some boys ate fruits, sandwich and cake. Most students believed that buffet is necessary at school and considered its condition from moderate to bad. More than half of them stated that the snacks and foods in buffets were invariable, expensive, unhealthy and nonnutritive. Conclusion With respect to undesirable snack patterns of students, improving the condition of school buffets to have more nutritious foods is a significant step in altering eating habits of them. Keywords: Adolescent, Snack, Buffet, Focus group discussion (FGD)